Generation news: Consuming, sharing, and producing news across generations in five Johannesburg households - Silber, Gerson Russel (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This study sets out to explore the meaning, extent, and impact of the generational divide, between so-called Baby Boomers and their Millennial offspring, on the way news is accessed, consumed, shared, and produced in five purposively selected households in the Johannesburg area. Aside from these widely-used generational identifiers, Baby Boomers and Millennials are also commonly referred to as Digital Immigrants and Digital Natives, respectively. However, in a world where smartphones have become commonplace, and internet connectivity via fixed broadband and mobile data is ubiquitous, it can be argued that digital technologies now serve as a link, or perhaps even a bridge, between younger and older generations living in the same household. The study aims to put this proposition to the test, by interrogating the role of news as a conduit for storytelling and information-sharing in environments where each occupant will typically be using their own devices, with a wide variety of personally-curated news sources and platforms at their fingertips. This fragmentation or individualisation of access to news stands in sharp contrast to the communal traditions of the pre-Internet era, during which families would gather around the TV set to watch the evening newscast, or share sections of the Sunday newspaper according to their age and interest. This research, which seeks to address a gap in the literature of research into intra-generational news consumption in family households in the digital era, identifies points of intersection as well as diversion in media usage habits. An example of the former is the prevalence of WhatsApp as a centralised "meeting-point" for the sharing of useful, hyper-localised information within the family group, and beyond that, as a cross-generational news and discussion platform in its own right. On the opposite end of the spectrum, the study explores strict and seemingly counterintuitive divides between the generations, with some Millennial respondents rejecting social media platforms as "pointless and invasive, and some Baby Boomer parents embracing the platforms as forums for free expression and networking. In line with the key research question, which seeks to identify and analyse news usage and consumption across the generations in a selection of family households, the study considers the ways in which families in the digital era are creating a culture of shared interests and the active sharing of news, breaching the boundaries of their private spaces in a microcosm of the Habermasian public sphere of discourse and opinion.
Keywords: Baby boom generation -- South Africa; Generation Y -- South Africa; Conflict of generations -- South Africa Johannesburg; Generations -- South Africa Johannesburg; Digital media -- South Africa; Social media and journalism -- South Africa; Digital media Social aspects -- South Africa; News audiences -- South Africa